Penggantian Halogen ke LED pada Runway Edge Lights Bandara Ahmad Yani Sebagai Efesiensi Energi Listrik - Mukhtar, Andy Perdian; Desryanto, Nurhedhi (Jurnal Sains dan Teknologi Penerbangan, 2024)
Jenderal Ahmad Yani International Airport is an airport located in the West Semarang District, Semarang City. This airport has departure and arrival terminals that facilitate domestic and international flights. Ahmad Yani International Airport also has a runway (13-31) with a length of 2,560 meters. There is airport lighting system equipment whose function is to assist and serve aircraft taking off and landing so that they can operate in cloudy, cloudy weather and at night in the runway, taxiway and apron areas. One of the equipment in the airport lighting system is the runway edge lights. Currently, the runway edge lights installed at Jenderal Ahmad Yani International Airport still use halogen type lights, which require quite a large amount of electrical power and the electricity costs incurred are not small. Replacing halogen type runway edge lights with Light Emitting Diode (LED) runway edge lights as an effort to efficiently use electrical energy. In this study the author used a comparative method to determine the comparison of the efficiency of using electrical energy between the two types of LED runway edge lights and halogen runway edge lights. From the comparison data carried out, it can be concluded that replacing halogen runway edge lights with LED runway edge lights has been proven to increase the efficiency of electrical power usage over a long period of time. From the specification data, LED lamps have a longer life time, namely 56,000 hours compared to halogen lamps, which is only 1000 hours, so the savings are also greater. From power calculations, it can be seen that LED runway edge lights have more power efficiency than halogen runway edge lights. The total power of halogen runway edge lights (2 circuits) was 21,480.58 watts, while LED runway edge lights (2 circuits) decreased by 56.2% to 9,400.58 watts.